OVERVIEW OF HUMAN RIGHTS IN THE INDONESIAN CONSTITUTION - Kusdarini, Eny; Kemala, Vinna Dinda (Pancasila and Civics Education Journal (PCEJ), 2023)
The central point of constitutionalism is the problem of Right Fundamental humans. related to this, the role constitution is very important which is not only just to give guarantee and protection in a manner written, however Also to provide various values used by the institution of Justice in the interpretation and elaboration of rights. the Objective article explains the connection between the Constitution and the right of basic human which include content, meaning, place in the Constitution, and consequence arrangement of the right of basic man in the Constitution. The method of research used is the literature review method. Results study article This is put a right basic man in constitution No only make it as fundamental rights, but rather as right highest constitutional.